autoboot: a generator of bootstrap equations with global symmetry - Mocho Go; Yuji Tachikawa (Journal of High Energy Physics, 2019)
Abstract We introduce autoboot, a Mathematica program which automatically generates mixed correlator bootstrap equations of an arbitrary number of scalar external operators, given the global symmetry group and the representations of the operators. The output is a Python program which uses Ohtsuki’s cboot which in turn uses Simmons-Duffin’s sdpb. The code is available at https://github.com/selpoG/autoboot/ . In an appendix we also discuss a simple technique to significantly reduce the time to run sdpb, which we call hot-starting.